PENGARUH PERSEPSI KEMUDAHAN DAN KEGUNAAN TERHADAP NIAT ADOPSI CLOUD ACCOUNTING DI ERA DIGITAL - Hasbi, Baharudin Fardian; Hadiprajitno, Paulus Theodorus Basuki (Applied Research in Management and Business, 2025)
This study aims to analyze the factors influencing the intention to adopt cloud accounting (Accurate) among Micro, Small, and Medium Enterprises (MSMEs) in Kudus Regency using the Technology Acceptance Model (TAM) approach. The factors tested in this study are perceived usefulness and perceived ease of use, which influence the intention to adopt cloud accounting. This research uses a quantitative method with purposive sampling involving 240 respondents who are SME owners or managers. Data were collected through questionnaires and analyzed using Partial Least Squares (WarpPLS 8.0). The results show that perceived usefulness has a positive effect on the intention to adopt cloud accounting. Perceived ease of use also positively affects the intention to adopt cloud accounting. Furthermore, perceived ease of use positively influences perceived usefulness.